2019
DOI: 10.3390/en13010110
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LID Process with a Remote Direct Heating Method Using a Half-Bridge Resonance Circuit for a PERC Solar Cell Module

Abstract: As the importance of the levelized cost of electricity (LCOE) increases in the solar cell industry, the demand for high-efficiency solar cells is rapidly increasing. Typically, p-type passivated emitter rear contact (PERC) solar cells are the most commonly used in the industry, and their efficiency is approximately 22–23%. P-type solar cells are reported to exhibit a light-induced degradation (LID) phenomenon, in which their output constantly decreases during power generation under solar radiation, and the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…9, we determined for the c-Si solar cells an activation energy of Eact,mono ~0,42 eV. Previous studies have reported values in the range of 0.3 to 0.475 eV [27,33,34].…”
Section: Thermal Activation Energies Of the Defectsmentioning
confidence: 94%
“…9, we determined for the c-Si solar cells an activation energy of Eact,mono ~0,42 eV. Previous studies have reported values in the range of 0.3 to 0.475 eV [27,33,34].…”
Section: Thermal Activation Energies Of the Defectsmentioning
confidence: 94%